Meconium ileus equivalent in adults with cystic fibrosis of pancreas: a report of six cases. Issue 6039 (2nd October 1976) - Hodson, M E; Mearns, M B; Batten, J C
Abstract : Eleven episodes of "meconium ileus equivalent" have been seen in six adults with cystic fibrosis of the pancreas. Three patients were initially treated surgically; one died and the other two developed serious postoperative chest infections. Six episodes were successfully treated medically with acetylcysteine orally and by enema, nasogastric suction, and intravenous fluids. Operation should be avoided if possible, and maintenance treatment with acetylcysteine may be necessary to prevent relapse.